Pengembangan Handout Berbasis Konstektual Pada Materi Laju Reaksi Untuk SMA/MA - Sirry Alvina; Riska Imanda; Mellyzar Mellyzar; Zahratul Fitri (Peneliti.net, 2022)
This research aimed to develop contextual-based handouts on reaction rate material with valid, viable, and interesting responses used as teaching materials in the learning process. The development model used in this study is the Borg and Gall models. The validity of the handout developed is divided into two validity of material and media by 84.1% and 93% respectively. Responses from 6 teachers and responses based on the questionnaire given were 91.17% and 90.77%. Handout developed is applied in the learning process with a total of 20 learners using pretest and posttest. Data obtained by researchers using the N-gain formula to find out the improvement of cognitive learning after giving treatment with the number of N-gain scores is 0.513. Based on the hypothesis test with the t-test on the known output sig (2-tailed) = 0.000 < 0.005 then Ho was rejected, meaning there was a significant difference in learning outcomes before and after using contextually based handouts. Based on the data above it was concluded that the results of contextual-based handout development research can be declared valid, feasible, and the response is interesting and can improve the cognitive learning